2010
DOI: 10.1149/1.3414026
|View full text |Cite
|
Sign up to set email alerts
|

(2009 ECS Battery Division Technology Award) Development of Highly Durable PFSA Membrane for PEMFC under High Temperature and Low Humidity Conditions

Abstract: The world's first highly durable PFSA membrane for PEMFC have been developed, which can operate for more than 6,000 hours at 120ºC and 50% relative humidity (RH). The membrane is comprised of a newly invented composite polymer (NPC polymer), which has exceptional chemical stability against degradation caused by the hydroxyl radical even at 120ºC. This achievement has opened up a new era of operating PEMFC in the temperature range of near freezing to120ºC under low and high humidity conditions for an extended p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Moreover, many studies are suggested that the reaction of PFSA with hydroxyl radical which is generated by the operating PEFCs are depended on its humidity conditions (water content λ). For example, under low humidity conditions, it is important to considered not only the unzipping mechanism of polymer end group (such as -COOH) which was discussed by Curtin et al [1] but also the mechanism is started from the abstraction reaction of hydrogen at the sulfonic acid group in the side chain which was proposed by Endoh [2]. In order to clarify the details of this degradation mechanism, many studies have been carried out by theoretical approaches [3][4][5].…”
mentioning
confidence: 99%
“…Moreover, many studies are suggested that the reaction of PFSA with hydroxyl radical which is generated by the operating PEFCs are depended on its humidity conditions (water content λ). For example, under low humidity conditions, it is important to considered not only the unzipping mechanism of polymer end group (such as -COOH) which was discussed by Curtin et al [1] but also the mechanism is started from the abstraction reaction of hydrogen at the sulfonic acid group in the side chain which was proposed by Endoh [2]. In order to clarify the details of this degradation mechanism, many studies have been carried out by theoretical approaches [3][4][5].…”
mentioning
confidence: 99%